Evaluation of Seed-Borne Fungi of Pinus roxburghii - Rawat, P. S.; Punj, Nidhi; Joshi, Kirti; Harsh, N. S. K. (Indian Forester, 2006)
Seeds collected from different sources of Pinus roxburghii from Himachal Pradesh, Uttaranchal, J&K and Nepal were evaluated for the occurrence of seed mycoflora. A total of twelve species belonging to nine fungi were isolated of which species of Aspergillus and Penicillium were dominant. Seed source Rajgarh Himachal Pradesh was found to be infested with maximum number of eight fungi, while in seed source of Uttarkashi (Uttaranchal) two fungi namely A. niger and A. flavus were recorded.